What Makes the Harderian Gland Transcriptome Different From Other Chicken Immune Tissues? A Gene Expression Comparative Analysis - Deist, Melissa S.; Lamont, Susan J. (Frontiers in Physiology, 2018)
The Harderian gland is a sparsely characterized immune tissue known to play an important role in local immunity. The function of the Harderian gland, however, is not clearly defined. Measuring the expression of all genes using RNA-seq enables the identification of genes, pathways, or networks of interest. Our relative RNA-seq expression analysis compared the chicken Harderian gland transcriptome to other important primary and secondary immune tissues including the bursa of Fabricius, thymus, and spleen of nonchallenged birds. A total of 2,386 transcripts were identified as highly expressed in the Harderian gland. Gene set enrichment showed the importance of G-protein coupled receptor signaling and several immune pathways. Among the genes highly expressed in the Harderian gland were 48 miRNAs, a category of genetic elements involved in regulation of gene expression. Several identified miRNAs have immune related functions. This analysis gives insight to the unique immune processes inherent in the Harderian gland.